Zasady solidarności w nauce Jana Pawła II i w Strajku w Gdańsku w 1980 r. - Polańska, Aurelia (Annales. Etyka w Życiu Gospodarczym, 2009)
At the end of the XX century something extraordinary happened in history of Poland. Without using violence the country become independent and Soviet occupation was stopped. The phenomenon proved John Paul II’ s teachings that “peace is made of justice and solidarity”. This article is divided into two parts. The first one is about the principles of solidarity used during the 1980 strike in the Shipyard of Gdańsk. These principles enabled the strike leaders to hold talks with the communist authorities. The agreement was the key which freed the country from the Soviet occupation and eventually gave it its freedom. The second part of the article consists of a description of interhuman and international solidarity which is found in John Paul II’s works. His teaching during the 3rd pilgrimage to Poland that took place in 1987 and which was addressed mainly to the working people of Gdańsk and Gdynia had a great impact on Polish people. However after Poland regained its independence the idea of solidarity was forgotten. It could not be found in the reality described in newspapers or other mass media. It’s high time this changed. Scientists and journalists responsible for the picture of public life, should remind society of the solidarity principles. They should also show the advantages of using these rules in the national economy. Thus showing the way to a successful, peaceful development of work, economic development and well-being in our present day society.